PERAN KEPUASAN KONSUMEN MEMEDIASI HUBUNGAN KUALITAS PRODUK DAN PERSEPSI HARGA DENGAN KEPUTUSAN PEMBELIAN ULANG - Prayoni, Ida Ayu; Respati, Ni Nyoman Rsi (E-Jurnal Manajemen, 2020)
This study aims to determine the effect of product quality and price perception on consumer satisfaction and repurchase decisions on consumers who buy and use Pepsodent toothpaste. This research was conducted in Denpasar City with a sample size of 105 respondents with non-probability methods in the form of purposive sampling. Data collection was carried out through questionnaires with as many as 15 indicators measured using a Likert scale. Data analysis techniques used in this study are path analysis techniques with classical assumption test and sobel test. The results of the study stated that the variables of customer satisfaction, product quality variables and price perception variables had a positive and significant effect on repurchase decisions. Keywords : product quality, price perception, customer satisfaction, repeat purchase decisions